From caregiver to care receiver: scope review about workers' mental health in times of COVID-19 - Laguna, Gabriela Garcia de Carvalho (2023)
Introduction: The global health crisis triggered by the COVID-19 pandemic resulted in a higher prevalence of mental illness, especially among health professionals. Objective: To identify the relationship between Burnout Syndrome and mental illness in health workers during the COVID-19 pandemic and related risk factors in Brazil. Methods: This is a scope review, for which a search was carried out in 3 databases, applying the keywords (COVID-19) and (mental health workers), with a time frame for articles published between 2020 and 2022. Results: 18 of the 712 articles found were included. The analysis showed that the most frequent outcomes were increased prevalence of Burnout syndrome, depression, anxiety, sleep disturbances, stress symptoms and general psychological impact. The following are related aggravating factors: personal, structural aspects of the work environment and governmental aspects. Conclusions: The importance of further studies on the subject is highlighted, including long-term impact analyses.